Pháp luật và đạo đức Hồi giáo thời trung cổ - Reid, Megan H (Cambridge University Press, 2013)
Includes bibliographical references and index.; Introduction: devotional piety and islamic law -- The persistence of asceticism -- "Devote yourselves to deeds you can bear": voluntary fasting and bodily piety -- Charity, food and the right of refusal -- The devil at the fountain: problems in ritual -- Conclusion: Beyond transgression, beyond Sunna.